Increasing Human Resources Capacity Of Msme Markets Of Modern Tangereang South Tangereang - Aris Munandar; Masriah Masriah (Jurnal PKM Manajemen Bisnis, 2022)
The difficult situation during the pandemic has made the domestic economic situation chaotic, especially for small and medium-sized businesses. This service activity is a form of concern for the world of education towards environmental conditions, especially during the pandemic. Service activities are carried out at the BSD modern market, South Tangerang. The activity method is carried out by means of digital marketing training for small and medium business actors in the BSD modern market. In addition, the participants were invited to practice creating digital stores in various domestic marketplaces. Then also taught about how to make sales internationally through the ebay, alibaba, and amazon marketplaces. The result of this activity is to increase the knowledge of small and medium businesses in the modern market of BSD in marketing their products online. Then help open a digital store, so they can sell their products online.